Nitrate leaching from suction cup data: Influence of method of drainage calculation and concentration interpolation. Issue 2 (18th February 2020) - Vogeler, Iris; Hansen, Elly Møller; Nielsen, Svend; Labouriau, Rodrigo; Cichota, Rogerio; Olesen, Jørgen E.; Thomsen, Ingrid Kaag
Abstract: The use of suctions cups is a common practice for estimating nitrate (NO3 –N) leaching under agricultural systems despite the various uncertainties associated with the approach. One major uncertainty is water flux, which is required for calculating NO3 –N leaching loads from measured concentrations. Another problem is the interpolation of NO3 –N concentrations between measurement days. We investigated how differences in water flux, obtained from two different models (EVACROP and APSIM), affect NO3 –N leaching loads. The effect of interpolation of NO3 –N concentrations based on days or drainage was also addressed. The models were set up according to a 2‐yr field experiment with spring barley ( Hordeum vulgare L. Quinch) with different levels of N fertilization rates on a loamy soil at Flakkebjerg, Denmark. Due to small differences in measured NO3 –N concentrations between sequential samplings, the method of interpolation did not significantly affect NO3 –N leaching in the two periods investigated. Although there is no standard against which leaching losses from different approaches can be tested, results highlight that the modeling of water uptake as affected by N supply influences the amount of drainage and thus calculated NO3 –N leaching. Therefore, for experiments with varying N fertilization levels, the APSIM model, which accounts for N nutrition on crop water use, is likely more accurate. For common fertilization rates, the simpler EVACROP seems appropriate. Thus, when using suction cup data for testing models or for evaluating mitigation options for nitrate leaching, the use of an appropriate model for estimating water fluxes is important.